Bank liquidity-stress testing and Basel III implementation in Indonesia - Mohamad Adam; Taufik Taufik; Muhammad Aditya Erfiyan Prathama (Economic Journal of Emerging Markets, 2015)
This study analyzes the possibility of the implementation of the Basel III, namely the rules of banking sector. The population analyzed in this study comprises the 120 banks in Indonesia. The result shows that Indonesian banking sector has tremendous value if the Basel III standards is applied in Indonesia. Bank BCA has the lowest values with a score of 8.89 while Bank BRI has the highest value with a score of 9.68. This study concludes that the standard rules of Basel III would be able to be implemented in Indonesia.